"I Could Do It in My Own Time and When I Really Needed It": Perceptions of Online Pain Coping Skills Training For People With Knee Osteoarthritis. Issue 12 (27th November 2020) - Lawford, Belinda J.; Hinman, Rana S.; Nelligan, Rachel K.; Keefe, Francis; Rini, Christine; Bennell, Kim L.
Abstract : Objective: To qualitatively explore the perceptions and experiences of people with knee osteoarthritis (OA) who used an online automated pain coping skills training program (PCST). Methods: This was a descriptive qualitative study (based on interpretivist methodology) embedded within a randomized controlled trial. Individual semistructured interviews were conducted with 12 people with knee OA who had participated in an 8‐week automated online PCST program while also receiving exercise advice and support from a physical therapist via Skype. Interviews in this study focused specifically on the online PCST program, rather than the physical therapy component. Interviews were audiorecorded, transcribed verbatim, and thematically analyzed. Results: Five themes arose: 1) easy to understand and follow (clearly explained, presented well), 2) better able to cope with pain (controlling pain, helping relax, pacing self, incorporating skills into exercise program), 3) anonymity and flexibility (no judgement by clinician, work at own pace, accessibility), 4) not always relatable or engaging (some techniques not useful, Americanization of the program, annoying character examples, time consuming and slow‐paced), and 5) support from clinician desirable (follow‐up from a clinician would be beneficial, worked in tandem with physical therapist–prescribed exercise, desire referral to the program by a trusted source). Conclusion: People with knee OA had generally positive experiences using an online PCST program, suggesting that online PCST is a broadly acceptable and accessible way to help people with OA to manage their pain. User engagement may be enhanced by redesigning some aspects of the program and by provision of support from a clinician.